Soccer showdown - Zucker, Jonny (Zucker, Jonny. Rex Jones., 2007)
Fifteen-year-old Rex Jones and his friends Dave and Carl are transported by Rex's mysterious cell phone onto a soccer team that is headed for the championships--if they can avoid being killed by a bully on the opposing team.